ANALYSIS OF CUSTOMER INTERESTS IN CHOOSING PRODUCTS SHARIA BANKING FOR FEBI STUDENTS AT UIN SMH BANTEN - Intan Riani; mukhammad fariz, Syifa; Putri Melani; Henny Saraswati; Wahyu Hidayat (Moneta: Jurnal Manajemen & Keuangan Syariah, 2023)
The purpose of this study is to analyze customer interest when choosing Islamic banking products among FEBI students at UIN SMH Banten. This research consists of 2 variables, one of which is Islamic banking products and customer interest. This study applies a quantitative approach through survey methods. Questionnaires were distributed to 30 FEBI students at UIN SMH Banten. After analyzing the data collected using descriptive and inferential statistical methods, this study indicates that customer interest in choosing Islamic banking products is very high. In addition, this study also reveals that there are several variables that influence customer interest in choosing Islamic banking products. These factors include trust in the Islamic banking system, service quality, suitability of products with Islamic values, and the level of benefits offered. In addition, this study also shows that when Islamic banks hold attractive programs for customers, they can influence customers' interest in choosing Islamic banking products.